Sequencing and validation of the genome of a Campylobacter concisus reveals intra-species diversity. - Nandan P Deshpande (Public Library of Science (PLoS), 2011)
Campylobacter concisus is an emerging pathogen of the human gastrointestinal tract. Its role in different diseases remains a subject of debate; this may be due to strain to strain genetic variation. Here, we sequence and analyze the genome of a C. concisus from a biopsy of a child with Crohn's disease (UNSWCD); the second such genome for this species. A 1.8 Mb genome was assembled with paired-end reads from a next-generation sequencer. This genome is smaller than the 2.1 Mb C. concisus reference BAA-1457. While 1593 genes were conserved across UNSWCD and BAA-1457, 138 genes from UNSWCD and 281 from BAA-1457 were unique when compared against the other. To further validate the genome assembly and annotation, comprehensive shotgun proteomics was performed. This confirmed 78% of open reading frames in UNSWCD and, importantly, provided evidence of expression for 217 proteins previously defined as 'hypothetical' in Campylobacter. Substantial functional differences were observed between the UNSWCD and the reference strain. Enrichment analysis revealed differences in membrane proteins, response to stimulus, molecular transport and electron carriers. Synteny maps for the 281 genes not present in UNSWCD identified seven functionally associated gene clusters. These included one associated with the CRISPR family and another which encoded multiple restriction endonucleases; these genes are all involved in resistance to phage attack. Many of the observed differences are consistent with UNSWCD having adapted to greater surface interaction with host cells, as opposed to BAA-1457 which may prefer a free-living environment.